2020
DOI: 10.3390/vetsci7030106
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the Enterotoxigenic Escherichia coli Infection Model for Post-Weaning Diarrhea by Controlling for Bacterial Adhesion, Pig Breed and MUC4 Genotype

Abstract: Enterotoxigenic Escherichia coli (ETEC) is a major cause of post-weaning diarrhea (PWD) in pigs and causes significant damage to the swine industry worldwide. In recent years, there has been increased regulation against the use of antibacterial agents in swine due to their health risks. Utilizing experimental models that consistently recapitulate PWD is important for the development of non-antibacterial agents against PWD in pigs. In this study, we established a highly reproducible PWD infection model by exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…It can cause many diseases such as severe diarrhoea and sepsis, and even life-threatening diseases under certain conditions. It has been shown that ETEC infection could result in an increased risk of mortality and even morbidity in children and young animals (1,26) .…”
Section: Discussionmentioning
confidence: 99%
“…It can cause many diseases such as severe diarrhoea and sepsis, and even life-threatening diseases under certain conditions. It has been shown that ETEC infection could result in an increased risk of mortality and even morbidity in children and young animals (1,26) .…”
Section: Discussionmentioning
confidence: 99%
“…First, lactylate or the LA + BM combination in the diet effectively reduced the relative abundances of F16 E. coli in the piglets in Phase 1, which has also been validated by the culture-dependent quantification method, as previously described. E. coli or ETEC are major pathogens that invade during lactation and the postweaning period, causing severe dysbiosis, increased intestinal permeability, diarrhea, and reduced growth performance [ 23 , 44 ]. Therefore, lactylate can help protect the piglets from E. coli infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, 40% of the challenged MUC4 resistant pigs in their study also developed challenge strain induced diarrhea a few days later. MUC4 resistant pigs that develop diarrhea after ETEC F4 challenge have been described recently [ 10 ]. We chose the MUC4 marker for comparison as it has been the most widely used genotype test for ETEC F4 susceptibility in challenge studies and is still being used [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%